Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan sub sektor kimia - Imam Hidayat; Khusnul Khotimah (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study was conducted with the aim of testing the effect of profitability and firm size on firm value. The population in this study used purposive sampling and used chemical sub-sector companies listed on the Indonesia Stock Exchange in the 2018-2020 period, based on the selection criteria, a sample of 13 companies were obtained which were used in this study. Statistical method used to test the hypothesis of multiple regression analysis. The results of this study indicate that profitability has no significant effect on firm value and firm size has a significant effect on firm value.